2010
DOI: 10.1016/j.scitotenv.2010.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Can sediment data be used to predict alkalinity and base cation chemistry of surface waters?

Abstract: We hypothesise that stream sediment elemental composition can predict mean and minimum concentrations of alkalinity, Ca and Mg in the river water throughout a river network. We tested this hypothesis for the River Derwent catchment in North Yorkshire, England, by using 6 years of water chemistry data from the Environment Agency and a digital elevation model to flow pathweight British Geological Survey (BGS) sediment element concentration data.The predictive models for mean concentrations were excellent for Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…When sampling commenced in the late 1960s the work was stimulated by, and oriented towards, mineral exploration, but this high-resolution survey has evolved continuously and now has many environmental applications. The geochemical mapping, originally based on the collection of wet-sieved drainage sediments (sub-150 µm fraction) at a target sampling density of one stream sediment sample per square kilometre, has expanded to include the sampling and analysis of stream waters and soils (sub-2 mm fraction) and now also includes the systematic high-resolution sampling of urban soils (Fordyce et al, 2005) publications have shown how widely these regional geochemical data can be used: to interpret subtle geological changes (Stone et al, 2004;Breward et al, 2011); to demonstrate the relationships between soils, heavy metal pollution and parent material (Breward, 2003, 2007, Johnson et al, 2011and Rawlins et al, 2003; glaciation studies (Scheib et al, 2011); in bioaccessibility studies (Palumbo-Roe et al, 2005); in archaeology (Chenery et al, 2001); environmental radioactivity (Jones et al, 2009); surface water quality research (Begum et al, 2010); and to better inform legislation such as defining normal levels of contaminants in soils for the UK Part 2A contaminated land Statutory Guidance (Johnson et al, 2012).…”
Section: The G-base Regional Geochemical Survey Projectmentioning
confidence: 99%
“…When sampling commenced in the late 1960s the work was stimulated by, and oriented towards, mineral exploration, but this high-resolution survey has evolved continuously and now has many environmental applications. The geochemical mapping, originally based on the collection of wet-sieved drainage sediments (sub-150 µm fraction) at a target sampling density of one stream sediment sample per square kilometre, has expanded to include the sampling and analysis of stream waters and soils (sub-2 mm fraction) and now also includes the systematic high-resolution sampling of urban soils (Fordyce et al, 2005) publications have shown how widely these regional geochemical data can be used: to interpret subtle geological changes (Stone et al, 2004;Breward et al, 2011); to demonstrate the relationships between soils, heavy metal pollution and parent material (Breward, 2003, 2007, Johnson et al, 2011and Rawlins et al, 2003; glaciation studies (Scheib et al, 2011); in bioaccessibility studies (Palumbo-Roe et al, 2005); in archaeology (Chenery et al, 2001); environmental radioactivity (Jones et al, 2009); surface water quality research (Begum et al, 2010); and to better inform legislation such as defining normal levels of contaminants in soils for the UK Part 2A contaminated land Statutory Guidance (Johnson et al, 2012).…”
Section: The G-base Regional Geochemical Survey Projectmentioning
confidence: 99%
“…The spatial and seasonal water quality variations in the context of chemical properties are influenced at regional scales because of many factors ( Begum et al . 2010 ; Rothwell et al .…”
Section: Introductionmentioning
confidence: 99%
“…The spatial and seasonal water quality variations in the context of chemical properties are influenced at regional scales because of many factors (Begum et al 2010;Rothwell et al 2010;Wang et al 2015). The water quality is significantly affected by inorganic pollutants like acids, salts, toxic metals; biological pollutants like protozoans, viruses and bacteria; various anions and cations like sulphates, phosphates, nitrates, calcium, magnesium and fluoride; and water-soluble substances emitting radiations (radioactive material).…”
Section: Introductionmentioning
confidence: 99%